2022
DOI: 10.24272/j.issn.2095-8137.2021.249
|View full text |Cite
|
Sign up to set email alerts
|

Capsid protein from red-spotted grouper nervous necrosis virus induces incomplete autophagy by inactivating the HSP90ab1-AKT-MTOR pathway

Abstract: As a highly important fish virus, nervous necrosis virus (NNV) has caused severe economic losses to the aquaculture industry worldwide. Autophagy, an evolutionarily conserved intracellular degradation process, is involved in the pathogenesis of several viruses. Although NNV can induce autophagy to facilitate infection in grouper fish spleen cells, how it initiates and mediates autophagy pathways during the initial stage of infection is still unclear. Here, we found that red-spotted grouper NNV (RGNNV) induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…However, SWAP70 expression showed no obvious change after the treatment with chloroquine or MG132 in the presence of cycloheximide and phenylephrine compared with the control group (Figure 2D ), suggesting that the increased SWAP70 protein expression after phenylephrine treatment can be ascribed to its reduced lysosomal degradation. To explore the possible upstream molecule(s) involved in the lysosomal regulation of SWAP70 protein expression, we performed protein mass spectrometry, intersected it with a subcellular localization database ( https://compartments.jensenlab.org/Search ) by bioinformatics to find the molecules that can colocalize with lysosomes (9 molecules remained after this step), and finally used a protein database ( https://www.uniprot.org ) to inquire about the function of these 9 molecules and gained 3 of them that were reported to involve in the regulation of molecular degradation 31 , 32 , 33 (Figure 2E ). Further experiments in human embryonic kidney 293T cells transfected with the indicated molecules suggested that granulin precursor (GRN) regulated the lysosomal degradation of SWAP70 (Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…However, SWAP70 expression showed no obvious change after the treatment with chloroquine or MG132 in the presence of cycloheximide and phenylephrine compared with the control group (Figure 2D ), suggesting that the increased SWAP70 protein expression after phenylephrine treatment can be ascribed to its reduced lysosomal degradation. To explore the possible upstream molecule(s) involved in the lysosomal regulation of SWAP70 protein expression, we performed protein mass spectrometry, intersected it with a subcellular localization database ( https://compartments.jensenlab.org/Search ) by bioinformatics to find the molecules that can colocalize with lysosomes (9 molecules remained after this step), and finally used a protein database ( https://www.uniprot.org ) to inquire about the function of these 9 molecules and gained 3 of them that were reported to involve in the regulation of molecular degradation 31 , 32 , 33 (Figure 2E ). Further experiments in human embryonic kidney 293T cells transfected with the indicated molecules suggested that granulin precursor (GRN) regulated the lysosomal degradation of SWAP70 (Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in L. japonicus brain (LJB) cells shows that CP blocks the interaction of AKT with HSP90ab1 by the competitive binding with HSP90ab1 to inhibit the AKT-mTOR pathway. 109 Moreover, grass carp reovirus (GCRV) infection evokes autophagy activation by eliciting ROS accumulation in Ctenopharyngodon idella kidney (CIK) cells. In this process, HSP70 promotes high-mobility group box 1b (HMGB1b)-Beclin1-mediated antiviral autophagy.…”
Section: Modulation Of Autophagy By Aquatic Rna Virusesmentioning
confidence: 99%
“…More deeply, the major autophagy‐inducing peptides of the G of VHSV and IHNV were identified by a pepscan technique 112 . A recent study shows that the N‐terminal arginine‐rich motif (N‐ARM, residue 1–33), arm (residue 34–51) and linker region (LR) domains of capsid protein (CP) are sufficient for red grouper nervous necrosis virus (RGNNV) to induce autophagy 109 . It is suggested that these protein regions could be a crucial target for the development of antiviral agents.…”
Section: The Roles Of Autophagy In Aquatic Animal Virus Infectionmentioning
confidence: 99%
“…Several studies have shown that lithium inhibits inositol monophosphatase and decreases the synthesis of inositol triphosphate, thereby regulating protein kinase B (AKT) to promote cell growth, proliferation, and anabolism ( Hermida et al, 2017 ; Malhi & Outhred, 2016 ; Zhang et al, 2022 ). Moreover, lithium has been shown to enhance AKT phosphorylation and inhibit glycogen synthase kinase-3 (GSK-3) ( Beaulieu et al, 2004 ; Liu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%